Studi Implementasi Kebijakan Keselamatan dan Kesehatan Kerja Pertambangan pada Perusahaan Tambang Batuan di Kabupaten Keerom Provinsi Papua - Jhon Awawata; Endang Hartiningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to select four Mining Companies that have the best implementation of Occupational Safety and Health and to identify the implementation of Occupational Safety and Health that has been carried out by the Company so that it can be assessed as a whole. Therefore, data collection in this study was carried out by conducting observations, interview sessions with employees and observations of locations that have been selected as research objects as primary data and making location maps as secondary data. 4 (Four) Companies selected as research objects are located in SG Village Arso Satu Keerom Regency, Papua Province. The results showed that there were 4 (Four) companies that became the object of research, namely CV. SG, CV. ABC, CV. CTT Keerom and CV. JT XXX of the four Rock Mining companies have not implemented the Occupational Safety and Health Policy in the work environment in the Company. For this reason, it is hoped that the Keerom Regency government can pay attention to this matter.